Validated outcome of treatment changes according to International League Against Epilepsy criteria in adults with drug‐resistant focal epilepsy. (13th March 2019) - Mula, Marco; Zaccara, Gaetano; Galimberti, Carlo Andrea; Ferrò, Bruno; Canevini, Maria Paola; Mascia, Addolorata; Mecarelli, Oriano; Michelucci, Roberto; Pisani, Laura Rosa; Specchio, Luigi Maria; Striano, Salvatore; Perucca, Emilio
Summary: Objective: Although many studies have attempted to describe treatment outcomes in patients with drug‐resistant epilepsy, results are often limited by the adoption of nonhomogeneous criteria and different definitions of seizure freedom. We sought to evaluate treatment outcomes with a newly administered antiepileptic drug (AED) in a large population of adults with drug‐resistant focal epilepsy according to the International League Against Epilepsy (ILAE) outcome criteria. Methods: This is a multicenter, observational, prospective study of 1053 patients with focal epilepsy diagnosed as drug‐resistant by the investigators. Patients were assessed at baseline and 6, 12, and 18 months, for up to a maximum of 34 months after introducing another AED into their treatment regimen. Drug resistance status and treatment outcomes were rated according to ILAE criteria by the investigators and by at least two independent members of an external expert panel (EP). Results: A seizure‐free outcome after a newly administered AED according to ILAE criteria ranged from 11.8% after two failed drugs to 2.6% for more than six failures. Significantly fewer patients were rated by the EP as having a "treatment failure" as compared to the judgment of the investigator (46.7% vs 62.9%, P  < 0.001), because many more patients were rated as "undetermined outcome" (45.6% vs 27.7%, P  < 0.001); 19.3% of the recruited patients were not considered drug‐resistant by the EP. Significance: This study validates the use of ILAE treatment outcome criteria in a real‐life setting, providing validated estimates of seizure freedom in patients with drug‐resistant focal epilepsy in relation to the number of previously failed AEDs. Fewer than one in 10 patients achieved seizure freedom on a newly introduced AED over the study period. Pseudo drug resistance could be identified in one of five cases.